2018
DOI: 10.1111/jfpe.12966
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Gaussian process regression, artificial neural network, and response surface methodology modeling approaches for predicting drying time of mosambi (Citrus limetta) peel

Abstract: In this study, drying kinetics of mosambi peel was studied. The effect of three variables viz., temperature (50, 58, 70, 82, and 90 C), salt concentration (2, 5, 8, and 10%), and thickness of drying bed (1, 2, 3, and 4 mm) on drying time was determined by the central composite design.Applicability of Gaussian process regression (GPR)-based approach for modeling drying kinetics was analyzed. GPR-based model was compared with the commonly used approaches like artificial neural network (ANN) and response surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 26 publications
5
25
0
Order By: Relevance
“…ANN has been used to predict hot air convective drying of carrot (Erenturk & Erenturk, ) and pistachio (Tavakolipour & Mokhtarian, ) and drying behavior of heat pump assisted fluidized bed drying of canola seed (Malekjani, Jafari, Rahmati, Zadeh, & Mirzaee, ), onion (Jafari, Ganje, Dehnad, & Ghanbari, ), and green bell pepper(Jafari, Ghanbari, Ganje, & Dehnad, ). ANN was also applied to model the drying kinetics in different drying techniques such as microwave‐hot air drying of mushroom (Omari, Behroozi‐Khazaei, & Sharifian, ), hot air drying of mosambi peel (Chaurasia, Younis, Qadri, Srivastava, & Osama, ), open sun drying figs (Şahin & Öztürk, ), and infrared drying of mahaleb puree (Isleroglu & Beyhan, ). Genetic algorithm (GA) is an adaptive heuristic search algorithms based on the ideas of natural selection and genetics that is used to generate solutions for optimization problems and search problems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ANN has been used to predict hot air convective drying of carrot (Erenturk & Erenturk, ) and pistachio (Tavakolipour & Mokhtarian, ) and drying behavior of heat pump assisted fluidized bed drying of canola seed (Malekjani, Jafari, Rahmati, Zadeh, & Mirzaee, ), onion (Jafari, Ganje, Dehnad, & Ghanbari, ), and green bell pepper(Jafari, Ghanbari, Ganje, & Dehnad, ). ANN was also applied to model the drying kinetics in different drying techniques such as microwave‐hot air drying of mushroom (Omari, Behroozi‐Khazaei, & Sharifian, ), hot air drying of mosambi peel (Chaurasia, Younis, Qadri, Srivastava, & Osama, ), open sun drying figs (Şahin & Öztürk, ), and infrared drying of mahaleb puree (Isleroglu & Beyhan, ). Genetic algorithm (GA) is an adaptive heuristic search algorithms based on the ideas of natural selection and genetics that is used to generate solutions for optimization problems and search problems.…”
Section: Introductionmentioning
confidence: 99%
“…ANN was also applied to model the drying kinetics in different drying techniques such as microwave-hot air drying of mushroom (Omari, Behroozi-Khazaei, & Sharifian, 2018), hot air drying of mosambi peel (Chaurasia, Younis, Qadri, Srivastava, & Osama, 2018), open sun drying figs (Şahin & Öztürk, 2018), and infrared drying of mahaleb puree (Isleroglu & Beyhan, 2018). Genetic algorithm (GA) is an adaptive heuristic search algorithms based on the ideas of natural selection and genetics that is used to generate solutions for optimization problems and search problems.…”
mentioning
confidence: 99%
“…Yang et al (2007) also employed Hummeida K ‐value model and modified Oswin EMC model to study the thin layer drying of peanut, which showed good prediction. Furthermore, artificial neural network (ANN) had successfully described the drying kinetics of rice (Alam et al, 2018; Beigi, Torki‐Harchegani, & Tohidi, 2017), mosambi peel (Chaurasia, Younis, Qadri, Srivastava, & Osama, 2018) and quince (Taghinezhad, Kaveh, Jahanbakhshi, & Golpour, 2020). However, Faridi, Golian, Mottaghitalab, López, and France (2013) reported that the predictive ability of ANN models showed poor predictive performance on newly introduced data.…”
Section: Introductionmentioning
confidence: 99%
“…They are effective in modeling complex, nonlinear processes. ANNs have been used in the food industry to model image-based classification (Kılıç, Boyacı, Köksel, & Küsmeno glu, 2007), drying of food products (Chaurasia, Younis, Qadri, Srivastava, & Osama, 2018;Erenturk & Erenturk, 2007;Guiné et al, 2015), modeling rheological properties of foods (Ramzi, Kashaninejad, Salehi, Mahoonak, & Razavi, 2015), and so forth. The Gaussian process regression (GPR) models are a powerful nonparametric Bayesian approach to regression.…”
mentioning
confidence: 99%
“…It uses theoretically infinite number of parameters to understand the inherent function in the training data (Schulz, Speekenbrink, & Krause, 2018). These models are simpler and easier to understand and can help in understanding the underlying function describing the data (Chaurasia et al, 2018).…”
mentioning
confidence: 99%